Emotions related to mergers and acquisitions : Discussion analyses of SSAB Ab–Rauraruukki Oyj and STX Finland Oy–Meyer Werft GmbH - Tikkakoski, Elina (fi=Turun yliopisto|en=University of Turku|, 2018)
There has been a wave of mergers and acquisitions during the past few decades. However, their failure rate remains high and poorly understood. Moreover, the M&A process is highly sensitive in nature. The pre-acquisition, combination and post-merger integration phases are in the core of this study due to these strong emotions evoked. Moreover, M&As are highly emotional event. Emotions are short-term, and have a certain trigger. Majority of management literature still overrides emotions. Despite the individuality of emotions, they are proved to be rather homogenous in an organisational change. Media provokes these emotions, and functions as a daily mirror. Thereby, newspaper articles have a big influence on employees’ emotions. In the case of cross-border M&As, cultural differences add their own spice to managing emotions. The purpose of this study is to increase understanding regarding the subject of how emotions are portrayed in the media in the case of cross-border mergers and acquisitions. It has been further divided into sub-objectives, to characterize what types of emotions are reflected in mergers and acquisitions and to analyze how these emotions evolve during the merger and acquisition process, and to further describe what are the triggers for these emotions. The purpose of the study was approached through both theory and applying it to practice through discussion analysis research strategy. The aim of this study was to describe real-life case events with time and space limitations, and thereby a qualitative approach was chosen. Moreover, a holistic approach was needed, and discussion analysis of two case studies was provided with a sample of 139 newspaper articles with reference to SSAB Ab–Rautaruukki Oyj merger or to STX Finland Oy–Meyer Werft GmbH acquisition. The articles were coded according to their content, based on what emotion or emotions was reflected in each article and they were targeted accordingly with the NVivo software. For the analysis, frameworks and decision rules were developed using the theories presented in the study. The analyzes of this study support the theory of M&As being highly emotional events, as various emotions, both positive, as for STX–Meyer, and negative, case SSAB–Rautaruukki, were reflected in the case M&As. These emotions evolve and differ in intensity as well as between the emotional tones throughout the phases of the deal. Triggers for these emotions are various, and they vary from case to case. However, common denominators often are, the newly combined organization, cultural differences in management styles or the management itself, the deal itself, the former parent companies of each party, or the collective emotions of the employees. This study has contributed in providing discussions on international M&As as well as on how the group emotions evolve and illustrations through the two, highly comparable yet so divergent case studies.